Perbaikan Tata Letak Fasilitas Produksi Pada UD. Tahu Goreng Sky Di Tebing Tinggi Dengan Metode Activity Relationship Chart - Dedy Ismail; Derlini Derlini (JURUTERA - Jurnal Umum Teknik Terapan, 2017)
Facility layout is a technique to arrange or placing the production facilities with the aim to facilitate the processing and increasing the production. This research focus on improving the Layout of Facilities that have not been well organized in the home industry UD. Tahu Goreng SKY Tebing Tinggi which produces fried tofu. In this research activity changes were made to the Size of the Work Area, the large Work Area, and Distance between Stations using the ARC (Activity Relationship Chat) method, subsequently depicted on the activity relationship map and designed in the Activity Relationship Diagram (ARD) worksheet to provide alternative changes / improvements layout of the home industry that been mentioned above. From the results of this study obtained changes in the area of work area namely 7.5 m2 immersion station, 6.25 m2 milling station, boiling station 7.84 m2, 4.68 m2 screening and opening station, 7.04 m2 pressing station, cutting station 4.29 m2, and 7.84 m2 frying station. The process flow pattern in the new layout changes to a U-shaped process flow from the previously indeterminate angle so as to simplify and facilitate the regular transfer of materials according to the production process flow more convenient and efficient